Comparative pharmacokinetics of danofloxacin in healthy and Pasteurella multocida infected ducks. Issue 6 (4th September 2018) - Xiao, Xia; Lan, Weixuan; Wang, Ying; Jiang, Lijie; Jiang, Yongjia; Wang, Zhiqiang
Abstract: Pasteurella multocida ( P. multocida ) infection causes substantial economic loss in the duck industry. Danofloxacin, a fluoroquinolone solely used in animals, shows good antibacterial activity against P. multocida . In this study, the in vitro pharmacodynamics of danofloxacin against P. multocida was studied. The serum and lung tissue pharmacokinetics of danofloxacin were studied in healthy and P. multocida infected ducks following oral administration of a single dose of 5 mg/kg body weight (b.w.). The MIC, MBC and MPC of danofloxacin against P. multocida (C48‐1 ) were 0.25, 1 and 3.2 μg/ml, respectively. The C max was 0.34 μg/ml, attained at 2.03 hr in healthy ducks, and was 0.35 μg/ml, attained at 2.87 hr in diseased ducks. Compared to the serum pharmacokinetics of danofloxacin in healthy ducks, the absorption rate and extent were similar in healthy and diseased animals. In contrast, the elimination rate was slower, with an elimination half‐life ( T 1/2β ) of 13.17 and 16.18 hr for healthy and infected animals, respectively; the AUCs in the two groups were 5.70 and 7.68 μg hr/ml, respectively, which means the total amount of drug in the circulation was increased in the infected ducks. The maximum concentration in lung tissues between healthy and infected animals was not significantly different (8.96 vs. 8.93 μg/g). However, the T max in healthy ducks was longer than that in infected ducks (4 hr vs. 1.75 hr), which means that the distribution rate of danofloxacin was slower in healthy ducks. The concentration of danofloxacin in lung tissues was approximately 24‐fold higher than that in the serum. In the serum pharmacokinetic profiles, the ƒAUC0‐24 hr /MIC was 18.19 in healthy ducks and was 25.04 in P. multocida infected ducks at the clinical recommended dose, which is far from the PK/PD target (125 hr) of fluoroquinolones. Danofloxacin, at a dose of 5 mg/kg b.w., seems to be insufficient for ducks infected with P. multocida, with an MIC equal to 0.25 μg/ml.